The Public Sector Pay Gap in France, Great Britain and Italy - Claudio Lucifora; Dominique Meurs (Institute for the Study of Labor (IZA), 2004)
We investigate public-private pay determination using French, British and Italian microdata. While traditional methods focus on parametric methods to estimate the public sector pay gap, in this paper, we use both non-parametric (kernel) and quantile regression methods to analyse the distribution of wages across sectors. We show that the public-private (hourly) wage differential is sensitive to the choice of quantile and that the pattern of premia varies with both gender and skill. In all countries the public sector is found to pay more low skilled workers with respect to the private sector, whilst the reverse is true for high skilled workers. The effects are more pronounced for females.
Keywords: C14; J45; J31; 330; wage differentials; public sector; quantile regression; Lohnstruktur; Öffentlicher Dienst; Besoldung; Privatwirtschaft; Schätzung; Frankreich; Grossbritannien; Italien